Can political speech foster tolerance of immigrants? - Schleiter, P; Tavits, M; Ward, D (Cambridge University Press, 2021)
Politicians frequently use political speech to foster hostility toward immigrants, a strategy that shapes political preferences and behavior and feeds the success of the populist right. Whether political speech can be used to foster tolerance of immigrants, however, remains unexplored. We identify three mechanisms by which political speech could increase tolerance: (1) stressing in-group conceptions that highlight commonalities with immigrants; (2) emphasizing inclusiveness as an in-group norm; and (3) providing information that counters anti-immigrant stereotypes. Using quotes from US politicians in two survey experiments, we find that pro-immigrant speech that stresses inclusive norms or counters negative stereotypes about immigrants leads to more tolerant attitudes (but not behavior) toward immigrants. These effects are small and detectable only in large samples.